Social identity, intergroup conflict, and conflict reduction - Ashmore, Richard D.; Jussim, Lee J.; Wilder, David, 1949- (Rutgers series on self and social identity, 2001)
Annotation How are group-based identities related to intergroup conflict? When and how do ethnic, religious, and national identities lead to oppression, violence, rebellion, war, mass murder, and genocide? How do intergroup conflicts change people's identities? How might social identity be harnessedin the service of reducing conflict between groups? The chapters in this book present a sophisticated and detailed interdisciplinary analysis of the most fundamental issues in understanding identity and conflict.